2023
DOI: 10.17582/journal.pjar/2023/36.1.20.35
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Morphological Identification and Characterization of Freshwater Green Algae Based on the Microscopic Technique in District Rawalpindi

Abstract: G reen algae are one of the most diverse groups of algae, with at least 7000 species (Nelson and Garcia-Pichel, 2021). Green algae are characterized by several distinct features including filaments, colonies, branched, motile, non-motile, and bladelike thallus (Leliaert et al., 2012). Chloroplast contained chlorophyll a, b and accessory pigments including carotenes and xanthophylls which are surrounded by double membrane with thylakoid arranged in lamellae. Pyrenoid are present and embedded in the chloroplast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…All morphological characteristics, including color, shape, pyrenoid, filamentous, branching, unbranched, unicellular, chloroplast arrangement, and presence or absence of mucilage sheath, were noted. Each species was captured on camera, and species were recognized by comparing the images to reliable sources of information (Minhas et al, 2023;Arguelles and Monsalud, 2017;Jacquemin et al, 2019).…”
Section: Microscopic and Experimental Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…All morphological characteristics, including color, shape, pyrenoid, filamentous, branching, unbranched, unicellular, chloroplast arrangement, and presence or absence of mucilage sheath, were noted. Each species was captured on camera, and species were recognized by comparing the images to reliable sources of information (Minhas et al, 2023;Arguelles and Monsalud, 2017;Jacquemin et al, 2019).…”
Section: Microscopic and Experimental Observationsmentioning
confidence: 99%
“…Both Cladophorales and Chaetophorales accounted for 3% of the total algal diversity (Ali et al, 2010). Similarly, 30 species of green algae from District Gujar khan, Rawalpindi (Minhas et al, 2023). Furthermore, Leghari (2001) conducted a study on green filamentous algae found in lakes and ponds of Sindh, identifying 31 species of Chlorophyta in freshwater and riverine lakes.…”
Section: Chroococcus Disperses (Keissler) Lemmermannmentioning
confidence: 99%
See 1 more Smart Citation